Accuracy of Pain Tolerance Self-assessment Versus Objective Pressure Sensitivity. Issue 9 (1st May 2023) - Haupt, Edward T.; Porter, Giselle M.; Charlton, Timothy; Thordarson, David
Abstract : Introduction: Effective treatment of postoperative pain after elective surgery remains elusive, and the experience of pain can be variable for patients. The patient's intrinsic pain tolerance may contribute to this variability. We sought to identify whether there was a correlation between subjective report of intrinsic pain tolerance and objective measurement of pressure dolorimetry (PD). We also sought to identify whether a correlation existed between PD and Patient Reported Outcome Measurement Information System (PROMIS) scores of pain intensity, physical function, and mood. PD is a validated, objective method to assess pain tolerance. Markers of general mental and physical health are correlated with pain sensitization and may also be linked to pain tolerance. Methods: PROMIS scores, dolorimetry measurements, and survey data were collected on 40 consecutive orthopaedic foot and ankle surgery patients at the initial clinic visit. Patients were included if they had normal sensation on the plantar foot and no prior surgery or plantar heel source of pain. Results: Objective dolorimetry data reflecting 5/10 pain for the patients were 24 N/cm 2 (±8.9). Patients estimated their pain threshold as 7.3/10 (±2.1). No correlation was found between objective and subjective pain threshold identified. A moderate negative correlation of R = −0.44 was observed regarding PROMIS-M with dolorimetry data ( P < −0.05). PROMIS-M score >60 had a significant decrease in pain threshold to 15.9 ± 8.5 N/cm 2 compared with 25.7 ± 8.9 N/cm 2 for those who were less depressed with a PROMIS<60 ( P < 0.05). Conclusion: Subjective pain tolerance is not correlated with the patient's own objective pain threshold or markers of mental health and should not be used to assist clinical decision making. PROMIS-M is inversely correlated with objective pain. Higher PROMIS-M scores are associated with a lower objective pain threshold. Level of Evidence: Level II-Lesser Quality Randomized Controlled Trial or Prospective Comparative Study.